Derivational and Inflectional Morphemes: A Morphological Analisis - Rugaiyah Rugaiyah (UIR Press, 2018)
This study was intended to describe the category of inflectional and derivational morphemes found in Reading Texts of 2013 Curriculum English Textbook for the X Grade of Senior High Schools Published by Ministry of Education and Culture. Morpheme is used to refer to the smallest unit that has meaning or serves a grammatical function in a language. The morphemes which can meaningfully stand alone are called free morphemes while the morphemes such as –er and –s, which cannot meaningfully stand alone are called bound morphemes. The design of this study was descriptive qualitative. The results of this study show that Derivational prefixes consist of inter-, eco-, un-, ar-, pre-, re-, pro-, be-, de-, in-, dis-, a-, ex-, auto-, mis-, agri-, em-, ap-, im- and al-. While, Derivational suffixes consist of four categories. Thus are nominal, verbal, adjectival, and adverbial suffixes. First, nominal suffixes, namely –ism, -ation, -al, -ing, -ist, -or, -ity, -er, -ance, -ment, -ion, -ess, -ium, -ature, -ry, -ant, -ce, -ive, -cy, -y, -r, -ge, and -ness. Second, Verbal suffixes, namely –n and –ize. Third, Adjectival suffixes, namely –al, -ly, -ous, -ing, -able, -ic, -ish, -ive, -ian, -ny, -less, -ed, -ary, -nese, -y, and –ful and the last is adverbial suffix –ly. Otherwise, the categories of inflectional morphemes that found in texts consist of Noun suffixes (plural) such as; –s, -ies, and –es, Noun suffixes (possessive) e.g; –s’ and -’s, Verb suffixes (3rd person singular) are –s and –es, Verb suffixes (past tense) are –ed and –d, Verb suffixes (past participle) such as; –n, -d, and -ed, Adjective suffixes (comparative) are –er, - r, and –ier and Adjective suffixes (superlative) are –st and –est. Therefore, based on the result of finding verb suffixes are not found.